2014
DOI: 10.3892/mmr.2014.2279
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 inhibits high glucose-induced Smad3 activation and attenuates epithelial-to-mesenchymal transition of peritoneal mesothelial cells

Abstract: Abstract. Heat shock proteins (HSPs) are molecular chaperones that were initially identified as proteins expressed following exposure of cells to environmental stress. However, the function of HSPs in epithelial-to-mesenchymal transition (EMT) of peritoneal mesothelial cells remains unknown. In the present study, the regulation of HSPs and their function in cell EMT, particularly in rat peritoneal mesothelial cells (RPMCs), and the surrounding glucose concentrations and the molecular mechanism involved were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…In addition, several reports have demonstrated that HSP70 inhibits TGF-β-induced EMT by decreasing Smad2 phosphorylation [191][192][193]. Furthermore, it has been shown that HSP70 prevents high glucose-induced EMT of peritoneal mesothelial cells by inhibiting Smad3 and Smad4 phosphorylation and reactive oxygen species (ROS) production [194]. These findings suggest dual role of HSP70 in EMT, where HSP70-peptide complexes support transition of tumor cells towards acquiring mesenchymal phenotype.…”
Section: Hsp70 In Metastasismentioning
confidence: 94%
“…In addition, several reports have demonstrated that HSP70 inhibits TGF-β-induced EMT by decreasing Smad2 phosphorylation [191][192][193]. Furthermore, it has been shown that HSP70 prevents high glucose-induced EMT of peritoneal mesothelial cells by inhibiting Smad3 and Smad4 phosphorylation and reactive oxygen species (ROS) production [194]. These findings suggest dual role of HSP70 in EMT, where HSP70-peptide complexes support transition of tumor cells towards acquiring mesenchymal phenotype.…”
Section: Hsp70 In Metastasismentioning
confidence: 94%
“…Galectin-1 can also mediate high glucose peritoneal dialysis solution-induced epithelial mesenchymal transition (EMT) in human peritoneal mesothelial cells and may be a new target for the prevention and treatment of peritoneal fibrosis (Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of Hsp70 in cancer cells appears to be the destruction of the Hsp70-dependent heterocomplexes of E-cadherin/catenins, which function like an anchor between neighboring cells [43]. Liu et al demonstrated that Hsp70 inhibits high-glucose-induced EMT by modulating Smad expression and activation in rat peritoneal cells [44].…”
Section: Discussionmentioning
confidence: 99%